Crystal structures of potassium trifluorido(4-methoxyphenyl)borate and potassium trifluorido(4-fluorophenyl)borate - Harrison, William T. A. (International Union of Crystallography, 2014)
The title compounds, K(+)·C(7)H(7)BF(3)O(−), (I), and K(+)·C(6)H(4)BF(4) (−), (II), are molecular salts containing para-substituted phenyltrifluoridoborate anions. In each compound, the B atom adopts a distorted tetrahedral BCF(3) geometry. Despite their different compositions and space groups, the irregular KF(8) coordination polyhedra of the potassium cations in the structures are almost identical. These polyhedra share faces and edges, generating infinite (010) layers in (I) and infinite (001) layers in (II). In (I), adjacent layers are stacked in an AAA… fashion, whereas in (II), they are stacked in an ABAB… sequence.